2010
DOI: 10.1063/1.3368698
|View full text |Cite
|
Sign up to set email alerts
|

Divacancies and the hydrogenation of Mg-Ti films with short range chemical order

Abstract: We obtained evidence for the partial chemical segregation of as-deposited and hydrogenated Mg 1−y Ti y films ͑0 Յ y Յ 0.30͒ into nanoscale Ti and Mg domains using positron Doppler-broadening. We exclusively monitor the hydrogenation of Mg domains, owing to the large difference in positron affinity for Mg and Ti. The electron momentum distribution broadens significantly upon transformation to the MgH 2 phase over the whole compositional range. This reveals the similarity of the metal-insulator transition for ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 23 publications
(41 reference statements)
4
33
0
Order By: Relevance
“…Upon hydrogenation, the S-parameter of the Mg 0.70 Ti 0.30 layer reduces significantly in the range of 1-5 keV in positron implantation energy, for which a substantial fraction of positrons annihilates in the metal (hydride) layer. The change in S-parameter is similar in magnitude as for the Mg to MgH 2 transformation in Mg [5][6][7] and Mg 0.90 Ti 0.10 films [7]. Our previous studies [5,15] demonstrated that such a large reduction in S-parameter is a direct result of the metal-insulator transition upon hydrogenation to the MgH 2 phase.…”
Section: Doppler Depth Profiling Of Metal Hydride Thin Filmssupporting
confidence: 54%
See 3 more Smart Citations
“…Upon hydrogenation, the S-parameter of the Mg 0.70 Ti 0.30 layer reduces significantly in the range of 1-5 keV in positron implantation energy, for which a substantial fraction of positrons annihilates in the metal (hydride) layer. The change in S-parameter is similar in magnitude as for the Mg to MgH 2 transformation in Mg [5][6][7] and Mg 0.90 Ti 0.10 films [7]. Our previous studies [5,15] demonstrated that such a large reduction in S-parameter is a direct result of the metal-insulator transition upon hydrogenation to the MgH 2 phase.…”
Section: Doppler Depth Profiling Of Metal Hydride Thin Filmssupporting
confidence: 54%
“…[7], we showed that the extracted positron lifetime of 312 ± 4 ps for the Mg film indicates that the positron trapping defect is the di-vacancy. The observed saturation trapping also accounted for the very short positron diffusion lengths of less than 5 nm for all Mg 1−y Ti y and Mg 1−y Ti y H x layers, as deduced by the VEPFIT analysis.…”
Section: Positron Lifetime Study On Vacancy-related Defectsmentioning
confidence: 96%
See 2 more Smart Citations
“…Three regimes where identified: (1) single fluorite phase for y < 0.87; (2) single phase rutile for y > 0.9 and (3) two phase coexistence for 0.87 < y < 0.90. The presence of a chemically partially segregated but structurally coherent metastable phase in Mg-Ti-H thin films was further confirmed by Extended X-ray Absorption Fine Structure (EXAFS) spectroscopy and by the positron Doppler broadening depth profiling method [94,95]. Positron depth-profiling was also applied to monitor the effects of hydrogenation on thin films [96].…”
Section: Binary and Ternary Mg-based Alloysmentioning
confidence: 99%